Kebijakan Kondisi Darurat Ketatanegaraan Perspektif Kaidah Fiqhiyah - Zamrud Lesmana; Mufidah Mufidah (STAATSRECHT: Indonesian Constitutional Law Journal, 2020)
Implementation of the state in practice, sometimes experiencing abnormalities (emergency). The legal system, which is generally used, is often unable to accommodate the interests of the state or society, so a separate arrangement is needed to move the functions of the state to run effectively. This paper discusses the constitutional emergency law in Indonesia according to statutory regulations and state of emergency constitutional principles fiqhiyah perspective. This research uses a qualitative method with a conceptual approach. The data in this study came from the 1945 Constitution of the Republic of Indonesia, Perppu No. 23 of 1959 and Law No. 24 of 2007 and the Fiqhiyah Rule. The results of the study stated that the policy in the state administration of Islam must be eliminated emergency conditions, both those that come from the internal state and external. The state of state emergency in Indonesia is regulated in such a way as to protect all its citizens in order to realize the ideals of the proclamation.